2015
DOI: 10.1016/s1002-0160(15)30058-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Responses to Biochars Varying in Particle Size, Surface and Pore Properties

Abstract: Biochars are known for their heterogeneity, especially in pore and surface structure associated with pyrolysis processes and sources of feedstocks. The surface area of biochar is likely to be an important determinant of the extent of soil microbial attachment, whereas the porous structure of biochar is expected to provide protection for soil microorganisms. Potential interactions between biochars from different sources and with different particle sizes were investigated in relation to soil microbial properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…In addition, biochar amendment reversed the reduction in soil microbial diversity caused by N addition (figure 3). One possible explanation may be that biochar created a favorable habitat for microbial colonization due to the large surface area and porous structure of biochar and its physicochemical properties, such as alkalinity, which might improve pH, water holding capacity and CEC (Jaafar et al 2015). These results support our second hypothesis by suggesting that biochar amendment could offset the positive effects of N deposition on MBC and the negative effects on bacterial diversity.…”
Section: Interaction Of Biochar Amendment and N Depositionsupporting
confidence: 78%
“…In addition, biochar amendment reversed the reduction in soil microbial diversity caused by N addition (figure 3). One possible explanation may be that biochar created a favorable habitat for microbial colonization due to the large surface area and porous structure of biochar and its physicochemical properties, such as alkalinity, which might improve pH, water holding capacity and CEC (Jaafar et al 2015). These results support our second hypothesis by suggesting that biochar amendment could offset the positive effects of N deposition on MBC and the negative effects on bacterial diversity.…”
Section: Interaction Of Biochar Amendment and N Depositionsupporting
confidence: 78%
“…Table 3 shows SBET, Vmicro, Vmeso and Vmacro. The surface area and porous structure provide potential habitats and are important factors in the char interaction with soil microorganisms and consequently, with their stability [ 40]. The two hydrochars showed higher surface areas than the pyrochars.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained the positive effects based on an improvement of soil physical properties, porosity, water holding capacity, pH and CEC resulting from the amendment of biochar. Jaafar et al [18] studied the response of arbuscular mycorrhizal towards biochar soil amendment and reported that application of 50 t/ha of biochar gave significantly higher colonization of mycorrhizal root for subterranean clover and wheat. Kameyama et al [19] reported that the addition of 1%-10% wt sugarcane bagasse biochar produced at 800˝C to two types of sandy soils in Japan increased the water retention capacity of the soils proportionally to the amount of biochar added.…”
Section: Introductionmentioning
confidence: 99%